Dynamic characterization of progressively damaged segmental masonry arches with one settled support: experimental and numerical analyses - Masciotta, Maria-Giovanna (2020)
This paper aims to explore the dynamic behavior of a segmental masonry arch subjected to increasing horizontal displacements of one support. To this end, output-only dynamic identification techniques are first used to track the evolution of the dynamic features of the system under progressive damage scenarios and evaluate their sensitivity to settlement-induced cracks. Considerations on the structural response of the segmental arch up to failure are also included. Then, a numerical procedure coupling linear perturbation and modal analysis is applied to simulate the dynamic behavior of the arch over consecutive scenarios, taking into account the influence of the damage on the structure's dynamic properties in an automatic way. The combination of experimental and numerical analyses allows to fully investigate the dynamics of the cracked masonry arch and to shed light on relevant aspects about the effects of settlement-induced cracks on the modal blueprints of masonry arches.